FUNGSI DAN PERAN LEMBAGA DESA DALAM PEMBANGUNAN INFRASTRUKTUR DESA DI KECAMATAN WANARAYA KABUPATEN BARITO KUALA - Wahidin Ilmi; Muhammad Akbar; Anhar Yani (STIA Bina Banua Banjarmasin, 2019)
The Function and Role of Village Institutions in Village Infrastructure Development in Wanaraya District, Barito Kuala Regency, Under the guidance of Muhammad Akbar as First supervisor and Anhar Yani as second counselor.This study aims (1) to Know the Description of the Function of Village Institutions in the Development of Village Infrastructure in the Wanaraya District of Barito Kuala Regency. (2) to Know the Role of Village Institutions in Village Infrastructure Development in Wanaraya District, Barito Kuala Regency. (3) To Know the Obstacles in the Implementation of the Function and Role of Village Institutions in Rural Infrastructure Development in Wanaraya District, Barito Kuala Regency.The approach of this research is a case study. In this study as key informants were the Camat, Kasi Community Empowerment, and Village Heads / Village Apparatus, Village Institution administrators and the community. Data is collected through interviews, observations and documents. The analysis used is qualitative analysis. The results showed that (1) Implementation of the Function and Role of Village Institutions in the Development of Village Infrastructure in Wanaraya Subdistrict which was divided into Developing and Disadvantaged Villages of Village Institutions that had not functioned and played a role in Implementing the Function and Role of Village Institutions in village infrastructure development in Wanaraya District Barito Kuala. This can be proven by the results of interviews of researchers with respondents that there are still many functions and roles of village institutions that are not visible, such as roles and functions in planning, implementation and supervision by village institutions in village infrastructure development (2) The role of village institutions in village infrastructure development is still not play a maximum role, there are a number of villages that have already walked but some other villages are still not running. This is evidenced by the results of interviews with the village head, there are still some indicators that have not been implemented in accordance with existing regulations. (3) Obstacles to the implementation of the Function and Role of Village Institutions in the development of village infrastructure there are several obstacles, such as in the case of human resources administered by Village Institutions, focusing on work to allowances for village institutions Fungsi dan Peran Lembaga Desa Dalam Pembangunan Infrastruktur Desa di Kecamatan Wanaraya Kabupaten Barito Kuala, Dibawah bimbingan Muhammad Akbar sebagai pembimbing Pertama serta Anhar Yani sebagai pembimbing kedua. Penelitian ini bertujuan (1) untuk Mengetahui Gambaran Fungsi Lembaga Desa Dalam Pembangunan Infrastruktur Desa di Kecamatan Wanaraya Kabupaten Barito Kuala. (2) untuk Mengetahui Peran Lembaga Desa Dalam Pembangunan Infrastruktur Desa di Kecamatan Wanaraya Kabupaten Barito Kuala. (3) Untuk Mengetahui Hambatan dalam Pelaksanaan Fungsi dan Peran Lembaga Desa Dalam Pembangunan Infrastruktur Desa di Kecamatan Wanaraya Kabupaten Barito Kuala.Pendekatan penelitian ini adalah studi kasus. Pada penelitian ini selaku key informan adalah Camat, Kasi Pemberdayaan Masyarakat, dan Kepala Desa/Aparatur Desa, pengurus Lembaga Desa dan masyarakat. Data dikumpulkan melalui wawancara, observasi dan dokumen. Analisa yang digunakan adalah analisis kualitatif. Hasil penelitian menunjukkan bahwa (1) Pelaksanaan Fungsi dan Peran Lembaga Desa dalam Pembangunan Infrastruktur Desa pada Kecamatan Wanaraya yang terbagi menjadi Desa Berkembang dan Tertinggal adanya Lembaga Desa yang belum berfungsi dan berperan dalam Pelaksanan Fungsi dan Peran Lembaga Desa dalam pembangunan infrastruktur desa. Ini dapat dibuktikan dengan hasil wawancara peneliti dengan responden masih banyak Fungsi dan Peran Lembaga Desa yang tidak terlihat, seperti peran dan fungsi dalam Perencanaan, Pelaksanaan maupun Pengawasan oleh lembaga desa dalam Pembangunan Infrasruktur Desa (2) Peran Lembaga Desa dalam pembangunan infrastruktur Desa juga masih belum berperan secara maksimal, ada beberapa desa yang sudah berjalan akantetapi beberapa desa lainnya masih belum berjalan. Hal ini dibuktikan dengan beberpa hasil wawancara bersama kepala desa, masih ada beberpa indikator yang belum berjalan sesuai dengan regulasi yang ada. (3) Hambatan pelaksanaan Fungsi dan Peran Lembaga Desa dalam pembangunan infrastruktur desa terdapat beberapa hambatan, seperti dalam hal SDM pengurus Lembaga Desa, fokus pekerjaan sampai tunjangan lembaga desa.